Combination of Q-Switched Nd:YAG and Fractional Erbium:YAG Lasers in Treatment of Melasma: A Randomized Controlled Clinical Trial - Alavi, Shiva; Abolhasani, Ehsan; Asadi, Sharin; Nilforoushzadeh, Mohammadali (Journal of Lasers in Medical Sciences, 2017)
Introduction: Ablative and nonablative lasers have been used to treat melasma. We aimed to assess and compare the combining Q-switched Nd:YAG laser (QSNYL) and fractional erbium:YAG laser (FEYL) with QSNYL alone in treatment of melasma. Methods: This randomized controlled clinical trial was performed in our Research Center during 2013-2014. Women with melasma and without a history of keloid formation, hypersensitivity to hydroquinone, or pigmentary changes due to laser therapy were randomly allocated to receive four sessions of either QSNYL-FEYL combination or QSNYL alone. All patients received topical treatment with Kligman’s formula. Before laser therapy and 4 weeks after the last treatment session, patients’ skin was assessed for changes in skin color, melanin content, and erythema intensity of melasma lesions quantitatively. Results: Finally, 21 patients in QSNYL-FEYL and 20 in QSNYL group (mean age, 38.57 [5.60] and 42.60 [8.44] years, respectively) completed study. The skin color had become lighter in both groups (mean [SD] percentage change of 56.95 [40.29] and 29.25 [13.20] in QSNYL-FEYL and QSNYL groups, respectively) with significantly better results in QSNYL-FEYL group (P = 0.006). Percentage of decrease of melanin content was significantly higher in QSNYL-FEYL group (22.01 [10.67] vs. 7.69 [4.75]; P < 0.001). After adjustment for baseline values, the post treatment intensity of erythema was significantly lower in QSNYL-FEYL group (P < 0.001). The patients reported no adverse events. Conclusion: QSNYL-FEYL was significantly more effective in decreasing melanin content of lesions than QSNYL and led to a lighter skin.